Variation in dietary intake and physical activity pattern as predictors of change in body mass index (BMI) Z-score among Brazilian adolescents* - Carla C. Enes; Betzabeth Slater (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
Objective: To assess whether changes in dietary intake and physical activity pattern are associated with the annual body mass index (BMI) z-score change among adolescents. Methods: The study was conducted in public schools in the city of Piracicaba, Sao Paulo, Brazil, with a probabilistic sample of 431 adolescents participating in wave I (2004) (hereafter, baseline) and 299 in wave II (2005) (hereafter, follow-up). BMI, usual food intake, physical activity, screen time, sexual maturation and demographic variables were assessed twice. The association between annual change in food intake, physical activity, screen time, and annual BMI z-score changes were assessed by multiple regression. Results: The study showed a positive variation in BMI z-score over one-year. Among variables related to physical activity pattern only playing videogame and using computer increased over the year. The intake of fruits and vegetables and sugar-sweetened beverages increased over one year, while the others variables showed a reduction. An increased consumption of fatty foods (β = 0.04, p = 0.04) and sweetened natural fruit juices (β = 0.05, p = 0.03) was positively associated with the rise in BMI z-score. Conclusions: Unhealthy dietary habits can predict the BMI z-score gain more than the physical activity pattern. The intake of fatty foods and sweetened fruit juices is associated with the BMI z-score over one year.